Do patients with invasive lobular breast cancer benefit in terms of adequate change in surgical therapy from a supplementary preoperative breast MRI? - Heil, Jörg; Golatta, Michael; Rom, Joachim; Schipp, Anne-Isabell; Harcos, Aba; Schneeweiss, Andreas; Rauch, Geraldine; Sohn, Christof; Junkermann, Hans (Annals of oncology, 2012)
Background: Breast magnetic resonance imaging (MRI) has been introduced in the preoperative management of invasive lobular breast cancer (ILC). We analysed if MRI leads to adequate changes in surgical management. Patients and methods: We carried out a single-centre retrospective confirmatory analysis of 92 patients with ILC and a preoperative breast MRI. By applying a blinded tumour board method, we analysed if surgical procedures were altered due to breast MRI. In case of alteration, we analysed whether the change was adequate according to the postoperative pathology findings. We considered an adequate rate of change >5% to be a clinically relevant benefit.Results: A change in surgical therapy due to the MRI findings occurred in 23 of 92 patients (25%). According to the postoperative pathology findings, this change was adequate for 20 of these patients (22%; 95% confidence interval [CI] 14%-31%, P < 0.0001). An overtreatment occurred for three patients (3%; 95% CI 0%-6%) who underwent a mastectomy following the results of breast MRI. Patients with larger tumours did likely benefit more from preoperative breast MRI. Conclusions: Patients with ILC might benefit from a preoperative breast MRI. Possible harm from overtreatment should be minimised by diligent use of preoperative histological clarification.
Published online: 02 April 2011
Gesehen am 16.04.2018